Accounting education literature review (2016). (June 2017) - Apostolou, Barbara; Dorminey, Jack W.; Hassell, John M.; Rebele, James E.
Highlights: We review articles published in six accounting education journals during 2016. The reviews are organized by curriculum, instruction, educational technology, students, and faculty. We offer suggestions for future accounting education research. Research rigor of empirical articles is analyzed. We synthesize the literature to facilitate research and instructional development. Abstract: This review of the accounting education literature includes 108 articles published during 2016 in six journals: (1) Journal of Accounting Education, (2) Accounting Education, (3) Advances in Accounting Education, (4) Global Perspectives on Accounting Education, (5) Issues in Accounting Education, and (6) The Accounting Educators' Journal . This article updates prior accounting education literature reviews by organizing and summarizing recent contributions to the accounting education literature. Articles are categorized into five sections corresponding to traditional lines of inquiry: (1) curriculum and instruction, (2) instruction by content area, (3) educational technology, (4) students, and (5) faculty. Suggestions for research in all areas are presented. Articles presenting instructional resources and cases published in the same six journals during 2016 are listed in appendices categorized by the appropriate content area.